Habit of Mind as Reflected in Applied Linguistics Research: An Analysis of Theses Writing by Undergraduate Students in EFL Teacher Education - Berlin Sibarani (Journal of Language, Literature and Teaching, 2020)
Habits of mind refers to collective thoughts shared by the members of a community which covers three aspects, they are the nature of knowledge and knowing the language, method of knowledge development, and rhetoric for the knowledge communication. Habits of minds develop as a result of learning. Personal belief governs the learning. Habits of minds or collective thought of Applied Linguistics researcher community shared by the undergraduate students of EFL education are incomplete.  This is indicated by the errors, mistake and misleading they made in writing the titles, research problems, review of related literature, research designs, subjects of the study, significances of the study, conceptual framework, data analysis, conclusions and suggestions. Habit of mind of the undergraduate students develops and the determinant factors of this development is personal belief of the students. Speeding up the acquisition of the habit of minds should be started from encouraging positive personal belief.